2015
DOI: 10.3389/fgene.2015.00042
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of silver nanoparticle resistance in Escherichia coli

Abstract: The recent exponential increase in the use of engineered nanoparticles (eNPs) means both greater intentional and unintentional exposure of eNPs to microbes. Intentional use includes the use of eNPs as biocides. Unintentional exposure results from the fact that eNPs are included in a variety of commercial products (paints, sunscreens, cosmetics). Many of these eNPs are composed of heavy metals or metal oxides such as silver, gold, zinc, titanium dioxide, and zinc oxide. It is thought that since metallic/metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 38 publications
7
198
3
2
Order By: Relevance
“…However, similar to antibiotics, prolonged exposure of bacteria to AgNPs may result in the development of resistant bacterial cells. For instance, E. coli K12 MG1655 strain has developed resistance toward AgNPs; however, the bacterium does not possess any Ag-resistance element (Graves et al, 2015). It is therefore necessary in future to carefully examining the development of Ag-resistance in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar to antibiotics, prolonged exposure of bacteria to AgNPs may result in the development of resistant bacterial cells. For instance, E. coli K12 MG1655 strain has developed resistance toward AgNPs; however, the bacterium does not possess any Ag-resistance element (Graves et al, 2015). It is therefore necessary in future to carefully examining the development of Ag-resistance in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…While most metal-based NPs are microbicidal to an array of bacteria, genetic alterations in bacteria may result in rapid evolution of resistance to Ag NPs, 31 whereas Al 2 O 3 NPs trigger increased expression of conjugation-promoting genes, thus promoting horizontal transfer of antibiotic resistance genes. NPs have been tailored to subdue resistance …”
Section: Synergistic Antibacterial Effects Of Nanomaterials With Antimentioning
confidence: 99%
“…[28][29][30] On the other hand, upsurge in resistance to Ag NPs has been reported due to genetic alterations in bacteria. 31 The deposition of silver 32 The high toxicity of CuO NPs causes oxidative lesions, while DNA damage induced by ZnO and TiO 2 NPs limits the efficacy of these NPs. Nonetheless, NPs have emerged as alternative antimicrobial approach to combat biofilms and for treating severe bacterial infections.…”
Section: Nanotechnology-based Therapeutic Interventions To Fight Nosomentioning
confidence: 99%
“…30 While some studies reported that metal nanoparticles did not result in obvious resistance in bacteria aer long-term exposure to them, 12,24 others found the opposite: Agresistant or metal nanoparticle-resistant bacteria can occur in a variety of circumstances and environments. [31][32][33][34] To help to avoid overdose and unnecessary exposure of these nanomaterials, it is important to understand the antimicrobial mechanism of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%